Simulation of microbial growth based on Euler’s method / Siti Humaira Mohd Jasni, Zaihar Yaacob and Zainatul `Asyiqin Samsu - Mohd Jasni, Siti Humaira; Yaacob, Zaihar; Samsu, Zainatul `Asyiqin (Universiti Teknologi MARA Shah Alam, 2024)
Microorganisms such as bacteria, fungi and yeast produce valuable metabolites when they are grown in suitable culture conditions. The cultivation condition affects the cell growth, metabolism, and product production in a sophisticated and nonlinear way. Therefore, in this research, the growth of Lactococcus lactis NZ9000 in response to the growth conditions was simulated using different growth models. The objective was to simulate the effect of temperature, agitation speed, carbon and nitrogen sources, on the cell growth using the exponential model, logistic, and Monod equations. All equations were solved according to the Euler’s method using MATLAB R2021a for simulation. The experimental data used for the simulation were from literature. The accuracy of the model was expressed as percentage relative error between the maximum value of experimental and simulated data. Simulation results show that the optimum conditions for cell growth was achieved at temperature 27 °C, agitation speed of 100 rpm with glucose and peptone as the carbon and nitrogen sources, respectively. The logistic equation’s maximum cell concentration yields the lowest percentage error of 0.33% for the effects of agitation and 6.40% for temperature. While Monod equation give the closest accuracy of 1.84% and 7.11% for carbon and nitrogen sources, respectively. Thus, it was shown that the complexity of the microorganism growth was able to be simulated using suitable model such as logistic equation with the lowest relative error.